Reconstruction Of Civilized Meaning In Pancasila: Analysis Study Of Naquib Al-Attas Thought - Sufratman, Sufratman; Lovat, Emeretus Terry; Awaludin, Asep (Analisis: Jurnal Studi Keislaman, 2022)
Indonesia has long made Pancasila an ideal as well as a way of life for the nation and state. But in fact, the phenomenon that has emerged among the community is actually the opposite, it can even be said it moves away from the spirit of Pancasila itself. This problem arises because of a mistake in understanding the concept of civilized, thus causing a loss of adab in the Indonesian people and nation. This research is a library research, using descriptive method. The results of the study found that the concept of adab Naqib al-Attas comes from the Islamic worldview, which means discipline of the spirit, mind, and soul. According to him, the three foundations of this civilized building must receive serious guidance through the ta'dib process. The goal is to produce attitudes and behaviours that reflect justice and wisdom, where someone is able to put things in their place. For this reason, the values of Pancasila, especially the civilized concept as ideals as well as a view of life for the nation and state, which conditions are Islamic values must be understood based on the Islamic worldview, in the context of realizing a just and civilized society.